Are additional intermodal terminals still desirable? An analysis for Belgium - Meers, Dries; Macharis, Cathy (European Journal of Transport and Infrastructure Research, 2014)
Recently, the number of intermodal barge/road and rail/road terminals in Western Europe has boomed, facilitating a growth of more sustainable hinterland freight transport. But currently, the question is raised if additional intermodal terminals are still desirable, if they can operate in an economically viable way and where they should be located in the existing transport network. The goal of this research was to find optimal terminal locations from a terminal operators’ perspective, maximizing the potential transhipment volumes in Belgium, without competing with the already established terminals. The developed methodology was tested for the Belgium infrastructure network, but can be applied to any network. Different locations are selected in a meta-analysis, but local conditions such as land availability and stakeholder approval should be investigated prior to setting up new terminal initiatives. In addition, the analysis shows that the selection of optimal terminal locations is highly influenced by the inclusion of transport time, next to market price, as a selection criterion.